A Blueprinting Approach to Service Innovation in Fancy Restaurant - Prabowo, Theresya Amelia; Tarigan, Liyandri Rasbina (Soegijapranata Catholic University, 2024)
This research focuses on operational efficiency and the importance of service blueprint in reducing the number of complaints and enhancing customer satisfaction. The research method employed is qualitative with a descriptive approach, involving ten consumers from a fancy restaurant in South Jakarta. The results indicate that there is a gap between the service received and the existing standard operating procedures (SOP). Several fail points within the service blueprint that need improvement were also identified. Furthermore, the study finds that by enhancing the elements within the service blueprint, the company can significantly increase customer satisfaction and reduce the number of customer complaints. The implications of this research provide guidance for luxury restaurants in designing services that are more responsive and customer-centric, thereby creating a competitive advantage in the market.